MEMBANGUN GENERASI SEHAT: EDUKASI PHBS PADA ANAK USIA DINI DI DESA PAKUSARI, KABUPATEN JEMBER - Dyan Wigati; Dina Trianggaluh Fauziah; Dwi koko pratoko; Wanda Tri Agustin; Rahmadania Affelia Dianto; Ayu Safitri; Carolyn Octavia Cornelyanto (Jurnal SADEWA, 2026)
Early childhood is highly vulnerable to health issues like diarrhea and infections due to poor implementation of Clean and Healthy Living Behavior (PHBS). This community service activity aimed to improve the knowledge, attitudes, and skills of preschool children in Kertosari Village, Jember, specifically in mastering proper handwashing and tooth-brushing techniques. The method employed interactive counseling combined with direct demonstrations using dental phantoms and educational brochures to accommodate the concrete learning characteristics of children. The program involved 20 children under the age of seven accompanied by their parents. The results indicated that while initial knowledge was low, the children demonstrated high enthusiasm and were able to correctly practice the six-step handwashing method and proper tooth-brushing after the intervention. Evaluation through parent questionnaires showed high satisfaction, confirming that the play-based demonstration method is effective for this age group. In conclusion, this activity successfully established a foundation for independent healthy habits in children, which is essential for long-term health quality. Continued implementation with diverse health topics is recommended to ensure sustainable behavioral change